2013
DOI: 10.1371/journal.pgen.1003316
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Diversity in the Levant Reveals Recent Structuring by Culture

Abstract: The Levant is a region in the Near East with an impressive record of continuous human existence and major cultural developments since the Paleolithic period. Genetic and archeological studies present solid evidence placing the Middle East and the Arabian Peninsula as the first stepping-stone outside Africa. There is, however, little understanding of demographic changes in the Middle East, particularly the Levant, after the first Out-of-Africa expansion and how the Levantine peoples relate genetically to each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
86
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 32 publications
17
86
1
Order By: Relevance
“…Samples from the GO community slightly overlapped with the Druze of Northern Israel. Within Lebanon, no clear separation was detected between communities (Figure 3b), but overlaps within each community (Christian and Muslim) were found as noted by Haber et al 8 Such results are consistent with the common ancestry illustrated by the shared ROH previously mentioned.…”
Section: Shared Individual Roh Regions and Population Structuresupporting
confidence: 90%
See 2 more Smart Citations
“…Samples from the GO community slightly overlapped with the Druze of Northern Israel. Within Lebanon, no clear separation was detected between communities (Figure 3b), but overlaps within each community (Christian and Muslim) were found as noted by Haber et al 8 Such results are consistent with the common ancestry illustrated by the shared ROH previously mentioned.…”
Section: Shared Individual Roh Regions and Population Structuresupporting
confidence: 90%
“…A mathematical calculation using the Malécot formula applied to genealogies, as well as consanguineous marriage statistics from previous studies, led to an F-value of 1.56% for a Lebanese population. 3,[7][8][9] Using biological methodologies, an F estimation was first calculated using a microsatellite panel and FEstim algorithm and was then improved using genome-wide single-nucleotide polymorphism (SNP) chip-based advanced algorithms. 5,6 These estimations were based on the genotyping of a large number of genetic markers to infer the individual genomic proportion that is homozygous by descent (HBD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the Druze cluster (containing four sub-populations: Galilee and Golan (this study), Carmel, and Lebanon) was distinct compared with other Middle-Eastern populations (Bedouins and Palestinians), suggesting that genetic stratification in the region is due to religious, rather than geographic barriers. 17 The Druze populations clustered closer to the European samples compared with Palestinians and Bedouins, and closer to Palestinians than to Bedouins, likely due to different levels of African ancestry. 18 Subsequent PC analysis of the four Druze groups alone ( Figure 4) revealed that all four groups are genetically distinct.…”
Section: Druze Form Distinct Middle-eastern Clusters In Pc and Admixtmentioning
confidence: 88%
“…To examine the genetic structure of the Druze population in the context of other populations, we combined the Druze data set generated in the present study (parents only) with an additional Lebanese Druze data set (25 individuals from Haber et al 17 ) and with data from the Human Genome Diversity Project (HGDP 15,19,20 ), containing Illumina 650k genotypes of 967 unrelated individuals from 56 world-wide populations, including Druze from the Carmel region in Israel. 19,20 After removing SNPs not existing on all platforms and SNPs with low call rate, a total of 183 381 SNPs were analyzed in 1043 unrelated individuals.…”
Section: Comparison Populationsmentioning
confidence: 99%